Lichtparcours Braunschweig 2000 : Internationale Lichtkunst an Braunschweiger Okerbrücken. - Auer, Gerhard; Bräcklein, Jürgen; Böhme, Ulrike; Herring, Carina; Hesse, Anja; Katase, Kazuo; Nobis, Beatrix; Seyfarth, Ludwig; Steffens, Werner; Kulturinstitut Braunschweig (Braunschweig : Stadt Braunschweig, Der Oberstadtdirektor, Kulturinstitut, 2000)
Mikolajczyk, Antoni ; Bartels, Thomas ; Fischer, Jürgen LIT ; Brdenk, Peter ; Kutscher, Vollrad ; Buren, Daniel ; Hausig, Daniel ; Shalev-Gerz, Esther ; Plessi, Fabrizio ; Kersalé, Yann ; Kubisch, Christina ; Katase, Kazuo ; Böhme, Ulrike ; Goulbier, Yvonne
biog. p. 42-43
Duits
Engels
Lichtparcours Braunschweig 2000, Braunschweiger Okerbrücken, Kulturinstitut Braunschweig, 3. Juni - 31. Oktober 2000
boek